The Effect Of Reward And Punishment To The Performance Of PT. Telesindo Shop Tanjungpinang Employees - Evita Sandra (Journal of Business and Management Review, 2021)
This study aims to determine the influence of awards and penalties for the performance of PT Telesindo Shop Tanjungpinang Employees. The population is 59 people with a sample of 59 employees of PT. Telesindo Shop Tanjungpinang Employees. The data analysis model uses descriptive analysis, data quality test( validity and reliability test) , multiple linear regression analysis, t test, F test and determinant coefficient test. The test results showed the performance of employees of PT. Telesindo Shop Tanjungpinang Employees with multiple linear regression method shows Y= -2,975 + 0.584 X1 + 0.761 X2 + e with the value of the regression coefficient of the reward variable (X1) = 0.584, the coefficient of regression of the penalty variable (X2) = 0.761. T test results obtained award variable (X1) t calculate > t table (4,862 > 2,003) and sig value. 0,000. Variable penalty (X2) t calculate > t table (2,413 > 2,003) and sig value. 0.019. The results showed that variable awards and punishments simultaneously and partially had a positive and significant effect on the performance of employees of PT. Telesindo Shop Tanjungpinang Employees, with contributions from R Square 0.383 or 38.3% of employee performance was affected by awards and penalties, while the remaining 61.7% were influenced by other factors that were not participated in this study.